2016
DOI: 10.1101/040303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZIKA - How Fast Does This Virus Mutate?

Abstract: The World Health Organisation has declared the present epidemic of infection with the Zika virus to be a Public Health Emergency of International Concern. The virus appears to have spread from Thailand to French Polynesia in 2013, and has since infected over a million people in the countries of South and Central America. In most cases the infection is mild and transient, but the virus does appear to be strongly neurotropic and the presumptive cause of both birth defects in foetuses and Guillain-Barr&eacute… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Nucleotide variations were too numerous to discuss here. With respect to amino acid variations, structural proteins showed several variations in their sequences revealing high mutational rate of the new ZIKV strains (28). Variations observed were classified into two categories, those that were seen in all 2015-2016 samples and variations that were strain-specific.…”
Section: Structural Regionmentioning
confidence: 99%
“…Nucleotide variations were too numerous to discuss here. With respect to amino acid variations, structural proteins showed several variations in their sequences revealing high mutational rate of the new ZIKV strains (28). Variations observed were classified into two categories, those that were seen in all 2015-2016 samples and variations that were strain-specific.…”
Section: Structural Regionmentioning
confidence: 99%
“…NS3 and NS5 inhibitors from other flaviviruses, may form the basis of ZIKV intervention strategies [16] . A study showed that in a viral genome of 10 272 bases mutation rate vary between 12 and 25 bases a year [17] .…”
Section: Molecular Evolutionmentioning
confidence: 99%
“…Especially in virus presenting RNA genome, nucleotide polymorphisms have long been noted as an evolutionary mechanism and indicate viral adaptation to the host [34,35]. The mutation rate of ZIKV was demonstrated to be between 12 and 25 bases per year and corresponds to 0.2% of total ZIKV genome [36]. On top of the mutation rate, recombination events also play an important role in virus evolution.…”
Section: Structural Properties Genetic Context and Evolutionmentioning
confidence: 99%